Microbial technology : current state, future prospects. (Great Britain : Cambridge University Press, 1979)
The changing scene in microbial technology; The physiology of single-cell protein (SCP) production; The physiology of metabolite over-production; The influence of microbial physiology on reactor design...
Keywords: Microbiology; Microbial technology